Gamestorming : a playbook for innovators, rulebreakers, and changemakers - Gray, Dave, ....-; Brown, Sunni, ....-; Macanufo, James, ....- (Sebastopol (Calif.) : O'Reilly, 2010)
Great things don't happen in a vacuum. But creating an environment for creative thinking and innovation can be a daunting challenge. How can you make it happen at your company? The answer may surprise you: gamestorming. This book includes more than 80 games to help you break down barriers, communicate better, and generate new ideas, insights, and strategies. The authors have identified tools and techniques from some of the world's most innovative professionals, whose teams collaborate and make great things happen. This book is the result: a unique collection of games that encourage engagement and creativity while bringing more structure and clarity to the workplace. Find out why -- and how -- with Gamestorming.
Keywords: Werk ; creativiteit